Analysis of Macroeconomic Factors on the Movement of the Stock Market: JEL Classification: E44; G12; G14; C22; F31 - Diana Diana; Nopiani Indah (Journal La Bisecoman, 2026)
This study aims to analyze the influence of macroeconomic variables consisting of Inflation, Gross Domestic Product (GDP), Interest Rates, Exchange Rates, and Unemployment Rates on the Composite Stock Price Index (IHSG) on the Indonesia Stock Exchange. This study employs a causal quantitative approach by observing monthly time series data from January 2015 to December 2024. Through saturated sampling, 120 secondary data observations were obtained, sourced from the Central Bureau of Statistics, Bank Indonesia, and the Indonesia Stock Exchange. Data analysis was conducted using multiple linear regression based on Ordinary Least Squares (OLS) which fulfilled the classical assumption tests. The results concluded that simultaneously, Inflation, GDP, Interest Rates, Exchange Rates, and the Unemployment Rate have a significant effect on the IHSG. Partially, GDP and the Exchange Rate were proven to have a significant positive effect on the IHSG. Conversely, Interest Rates and the Unemployment Rate have a significant negative effect. Meanwhile, the Inflation variable was proven to have no significant effect on the IHSG during the observation period. The implications of this study emphasize that real and monetary macroeconomic factors dominate asset valuation sentiment in emerging capital markets.